Paradigma Kepemimpinan Transformatif Menuju Madrasah Unggulan - Indah Nurrohmah; Fitri Wulandari (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2021)
The concept of leadership is still developing from time to time. Leadership theory also continues to evolve to find the most effective form of leadership in organizational management. In the 1980s, transformative leadership was born and is often referred to as an effective leadership model. In its preparation, this leadership concept uses a leader-follower perspective. Transformative leadership is claimed to be the most effective leadership pattern, which can achieve the main goals. Using a descriptive qualitative approach with library research methods, and analyzed using the theory of